Deciphering the Molecular Profile of Plaques, Memory Decline and Neuron Loss in Two Mouse Models for Alzheimer’s Disease by Deep Sequencing - Bouter, Yvonne; Kacprowski, Tim; Weissmann, Robert; Dietrich, Katharina; Borgers, Henning; Brauß, Andreas; Sperling, Christian; Wirths, Oliver; Albrecht, Mario; Jensen, Lars R.; Kuss, Andreas W.; Bayer, Thomas A. (Frontiers in Aging Neuroscience, 2014)
One of the central research questions on the etiology of Alzheimer’s disease (AD) is the elucidation of the molecular signatures triggered by the amyloid cascade of pathological events. Next generation sequencing allows the identification of genes involved in disease processes in an unbiased manner. We have combined this technique with the analysis of two AD mouse models. (1) The 5XFAD model develops early plaque formation, intraneuronal Aβ aggregation, neuron loss and behavioral deficits. (2) The Tg4-42 model expresses N-truncated Aβ4-42 and develops neuron loss and behavioral deficits albeit without plaque formation. Our results show that learning and memory deficits in the Morris water maze and fear conditioning tasks in Tg4-42 mice at 12 months of age are similar to the deficits in 5XFAD animals. This suggested that comparative gene expression analysis between the models would allow the dissection of plaque-related and -unrelated disease relevant factors. Using deep sequencing differentially expressed genes (DEG) were identified and subsequently verified by qRT-PCR. 19 DEGs were identified in presymptomatic young 5XFAD mice, and none in young Tg4-42 mice. In the aged cohort, 131 DEGs were found in 5XFAD and 56 DEGs in Tg4-42 mice. Many of the DEGs specific to the 5XFAD model belong to neuroinflammatory processes typically associated with plaques. Interestingly, 36 DEGs were identified in both mouse models indicating common disease pathways associated with behavioral deficits and neuron loss.